2017
DOI: 10.1007/s12192-017-0786-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship of piperine and its synthetic amide analogs for therapeutic potential to prevent experimentally induced ER stress in vitro

Abstract: Endoplasmic reticulum (ER) is the key organelle involved in protein folding and maturation. Emerging studies implicate the role of ER stress in the development of chronic kidney disease. Thus, there is an urgent need for compounds that could ameliorate ER stress and prevent CKD. Piperine and its analogs have been reported to exhibit multiple pharmacological activities; however, their efficacy against ER stress in kidney cells has not been studied yet. Hence, the goal of this study was to synthesize amide-subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…In various studies, the antioxidant and anti-inflammatory effects of piperine have been examined. It has been reported that piperine supplement caused a significant decline in H2O2 production stimulated by puromycin [30], enhanced antioxidant capacity and reduction of lipid peroxidation [14], diminished oxidative stress of the endoplasmic reticulum [19] and reduction of MDA and elevation of superoxide dismutase and glutathione peroxidase [17]. Also, the results of other studies suggest that piperine causes diminished expression of NF-κB, TNF-α and ICAM-1 in different models of inflammation as well as ischemia-reperfusion [16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In various studies, the antioxidant and anti-inflammatory effects of piperine have been examined. It has been reported that piperine supplement caused a significant decline in H2O2 production stimulated by puromycin [30], enhanced antioxidant capacity and reduction of lipid peroxidation [14], diminished oxidative stress of the endoplasmic reticulum [19] and reduction of MDA and elevation of superoxide dismutase and glutathione peroxidase [17]. Also, the results of other studies suggest that piperine causes diminished expression of NF-κB, TNF-α and ICAM-1 in different models of inflammation as well as ischemia-reperfusion [16].…”
Section: Discussionmentioning
confidence: 94%
“…It can also protect and reduce damages in brain ischemia-reperfusion [16], and lead acetate induced nephrotoxicity in rats [17]. Mechanistically, it has been shown that piperine decreases intercellular adhesion molecule-1 (ICAM-1), tumor necrosis factor alpha (TNF-α), indcible nitric oxide synthase (iNOS), and nuclear factor-κB (NF-κB) expression [16, 18], and inhibits cytochrome P450 activity and endoplasmic reticulum stress [19]. In a previous study, we found that piperine gavage resulted in diminished renal inflammation, oxidative stress, tissue damage, and functional disturbances following 30 min of ischemia and 24 h of reperfusion (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, piperine gavage reduced MDA and increased FRAP, reflecting its anti-oxidative properties. It has been shown that piperine supplementation considerably reduces puromycin induced H 2 O 2 production, 34 increases antioxidative capacity of tissues, decreases lipid peroxidation, 11 reduces endoplasmic reticulum oxidative stress 24 and augments superoxide dismutase and glutathione peroxidase from renal tissue following lead acetate induced nephrotoxicity. 18 Via its antioxidant effect, piperine is able to reduce the oxidative stress in renal tissue following IR, appearing as a decrease in MDA and an increase in FRAP.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Several studies have been performed on the mechanism of piperine, reporting that it acts by reducing the expression of ICAM-1, TNF-α, iNOS, and NF-κB, 17 , 19 , 20 inhibiting cytochrome P450 enzymes 21 and p-glycoprotein activities, 22 , 23 and preventing endoplasmic reticulum stress. 24 However, the protective effect of piperine against functional disturbances, inflammation, oxidative stress and tissue damages induced by renal IR is yet to be fathomed. Therefore, the objective of the present study was to assess the protective effects of piperine against renal damages induced by 30-min bilateral renal ischemia followed by 24-h reperfusion in rat.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial H/R injury is related to the activation of ERS-induced apoptosis and PIP was indicated to be involved in ERS progression ( 3 , 18 , 19 ). As an ER chaperone, GRP78 is crucial for myocardial apoptosis during H/R, particularly since ERS can drive the apoptotic cascade, including the activation of caspase-12 in a CHOP-dependent manner ( 3 ).…”
Section: Resultsmentioning
confidence: 99%